2019
DOI: 10.1186/s13052-019-0743-6
|View full text |Cite
|
Sign up to set email alerts
|

Cortisol, leptin and free leptin index (FLI) in newborns in the first days of life and their importance for body weight programming

Abstract: BackgroundBirth weight and leptin seem to be the factors responsible for early programming of body weight in later life. A marker for leptin action is free leptin index (FLI), which depends on soluble leptin receptor (Ob-Re) (FLI = leptin/Ob-Re). In the present article, we suggest that FLI is modulated partly by cortisol variations observed in newborns in the first days of life and is connected with their postnatal weight loss.MethodsThe study group consisted of 44 full-term newborns. Leptin, cortisol and Ob-R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…In contrast, our current study did not show a statistically significant relationship between SPX and leptin in both the blood of the umbilical cord as well as in the peripheral blood of healthy and obese mothers. The reason for the lack of correlation as well as significant changes between the groups of non-obese and obese women may be the date of collection (samples were taken on the day of delivery), where the mother’s body is exposed to many other factors that may affect the concentration of this peptide, such as stress factors or physiological changes of this peptide during pregnancy, where, as research has shown, the highest level of this adiponectin in blood serum occurs in the perinatal period [ 36 , 37 , 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, our current study did not show a statistically significant relationship between SPX and leptin in both the blood of the umbilical cord as well as in the peripheral blood of healthy and obese mothers. The reason for the lack of correlation as well as significant changes between the groups of non-obese and obese women may be the date of collection (samples were taken on the day of delivery), where the mother’s body is exposed to many other factors that may affect the concentration of this peptide, such as stress factors or physiological changes of this peptide during pregnancy, where, as research has shown, the highest level of this adiponectin in blood serum occurs in the perinatal period [ 36 , 37 , 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are reports on hormonal axes disturbances leading to metabolic syndrome [25]. Maternal obesity is implicated as another factor that may impair the development of the fetus [26]. However, epigenetic changes appear to be an essential element of fetal programming.…”
Section: Discussionmentioning
confidence: 99%
“…After birth, leptin levels in newborns (approximately 2.8 ng/mL; [ 58 ]) are crucial for postnatal developmental progress. In humans, the serum concentration of leptin begins to decrease during the first week of life (as low as 0.2 ng/mL; [ 59 ]) in parallel with a reduction in body weight [ 59 , 60 ]. This leptin–body weight reduction is linked with the growth of infants during their first year of life [ 59 ].…”
Section: Early Leptin For Future Cardiometabolic Outputmentioning
confidence: 99%